Arthroscopic treatment of displaced tibial eminence fractures using wire loop technique - Nirkhe, Rajat; Sheth, Hardik; Pathak, Subodh Kumar; Barve, Raghav; Gour, Sandeep Kumar; M., Prashanth Raj (International Journal of Research in Orthopaedics, 2018)
Background: Several techniques of arthroscopic treatment of tibial spine avulsion fractures have been described in the literature. We conducted a study to analyze the results of arthroscopic assisted wire loop technique for treatment of tibial spine avulsion in adults and pediatric patients. Methods: From June 2011 to December 2016, 52 patients with tibial spine fractures were surgically treated with arthroscopic reduction and wire loop fixation. Forty-four patients were adults and eight were in their pediatric age group. The age group ranged from 9 years to 52 years with the mean age of 26.2 years. 28 patients were type 2 and 24 were of type 3 fracture as classified by Myeres and Mckeever’s classification. The final analysis was done using clinical tests, radiological evaluation and International Knee Documentation Committee (IKDC) and Lysholm score. Results: At final follow-up, the mean IKDC and Lysholm knee scores were, 92 and 93 respectively. All patients had a complete functional recovery and were able to return to work and to resume their activities. Conclusions: Arthroscopic wire loop fixation is an excellent method for tibial eminence fracture in adults and children which gives excellent results in form of control tension on ACL on each side of avulsed fragment and also gives adequate mechanical strength for early rehabilitation.